PERGESERAN KEBIJAKAN DAN PARADIGMA BARU DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI DI INDONESIA - Sutopo Purwo Nugroho (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2003)
Integrated watershed management, which aims at restoration of a soundhydrologic regime in the watershed considering water resources utilization,appropriate landuse, water quality control and environmental conservation, is becoming crucially important in Indonesia. Because, the land degradation of watershed in Indonesia more increases every time. There is a growing concern that many parts of the Indonesia watershed will continue to face problems of watershed degradation. The basic problem in most watershed area, especially in Java, is too many people being concentrated on too small land base. Besides that, the causes of watershed degradation are complex and interrelated, such as too much emphasis being placed on economic growth in the management of natural resources, and the continuing presence of poverty, population growth, infrastructural and industrial development. Thus, the exisiting environmental problems and their overall impacts are not only biophysical in nature, but also social.The integrated watershed approach stresses the interaction of all activities that take place throughout the watershed. The strategy of watershed management approach uses new paradigm with people of participation and using community development in operational, practices and bottom up approach.